Characterization of glucose-crosslinked gelatin films reinforced with chitin nanowhiskers for active packaging development. (15th January 2022) - Etxabide, Alaitz; Kilmartin, Paul A.; Maté, Juan I.; Gómez-Estaca, Joaquín
Abstract: To find renewable and sustainable alternatives to reduce the severe environmental impact of single-use synthetic plastic packaging, glucose-crosslinked gelatin films containing different amounts of chitin nanowhiskers (CNWs) were prepared. CNWs were first prepared by acid hydrolysis of chitin from shrimps, and characterized (morphological and thermal properties), before their addition into film-forming formulations. The films were heat-treated to promote the chemical crosslinking Maillard reaction (MR), between glucose and gelatin. The films then became less soluble (from 100% to ∼10%), thermally more stable, had a notably improved UV–vis light absorption capacity, and presented significantly enhanced tensile strength (from 42 to 77 MPa) and Young's modulus (from 1476 to 2921 MPa), however, they also became less flexible (from 17% to 7%) and transparent. These property alterations were mainly related to changes in crystallinity, the MR and to a lesser extent, to the formation of noncovalent (electrostatic and hydrogen bonding) interactions between CNWs and gelatin. Furthermore, due to the formation of MR products, the films turned yellow/dark brown and released antioxidant compounds (inhibition ∼33%) while immersed in water, which gave the films their active properties (stabilization of free radicals). These films have considerable potential as reinforced active packaging films for renewable food packaging applications. Graphical abstract: Image 1 Highlights: Active and reinforced gelatin films were prepared. Maillard reaction induced primary and secondary active antioxidant functions. Chitin nanowhiskers increased the crystallinity of films. Films showed better thermal stability, Young's modulus, and tensile strength. Solubility of films was reduced and antioxidant active compounds were released.